Prevalence of undernutrition and effectiveness of a community-based nutritional support programme to reverse stunting among children under five years of age in an urban slum in Kolkata, India: findings of a one-year longitudinal study - Marcello S Scopazzini; Violette Raoult; Saumya Kuruttuparambil; Esther Sulkers (Journal of Global Health Reports)
# Background Stunting, defined as z-score height-for-age (HAZ) \< -2, is an important contributor to the burden of childhood undernutrition among slum-dwelling residents in India’s metropolitan areas. Calcutta Rescue (CR) is a non-governmental organisation that provides medical care and nutritional support to slum-dwellers in Kolkata, India. CR undertook a study in Liluah Bhagar, an urban slum, to 1) establish the prevalence of undernutrition among children under five years of age, 2) evaluate the impact of a pilot nutritional support programme on growth patterns of a consecutively selected group of stunted children, and 3) identify socio-economic predictors of stunting.